Русский язык в интернете: компьютерный сленг или элементарная безграмотность? - Рагрина, Ж. М.; Турковский, С. П.; Рагріна, Жанна Михайлівна; Турковський, Сергій Петрович; Ragrina, Z. M.; Turkovskiy, S. P. (Могилев. ин-т МВД, 2016., 2016)
Статья посвящена вопросам роли новейших компьютерных технологий в жизни человека. Рассматриваются специфические особенности языка общения в Интернете. Характеризуются средства и способы передачи информации. The article is devoted to the role of the modern computer technologies in human life. The specific features of the language of communication on the Internet are discussed. The ways of information transmission are characterized.
Russian language on the Internet: computer slang or ignorance?
Keywords: компьютерные технологии; компьютерный сленг; computer technologies; computer slang